2017
DOI: 10.1016/j.ccell.2017.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Organelle Specific O-Glycosylation Drives MMP14 Activation, Tumor Growth, and Metastasis

Abstract: Cancers grow within tissues through molecular mechanisms still unclear. Invasiveness correlates with perturbed O-glycosylation, a covalent modification of cell-surface proteins. Here, we show that, in human and mouse liver cancers, initiation of O-glycosylation by the GALNT glycosyl-transferases increases and shifts from the Golgi to the endoplasmic reticulum (ER). In a mouse liver cancer model, expressing an ER-targeted GALNT1 (ER-G1) massively increased tumor expansion, with median survival reduced from 23 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
105
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(110 citation statements)
references
References 57 publications
5
105
0
Order By: Relevance
“…The association of cancer invasion with tumor growth and metastasis was indicated by recent lysosomal proteases studies, including research on MMP-3 39 , 45 , MT1-MMP 40 , 46 , cathepsin B 47 , 48 , and cathepsin D 49 . Due to the significant effect of Arl8b on highly invasive cancer cells that survive IR, we sought to validate whether Arl8b is required for invasive tumor growth and metastasis in a mouse model.…”
Section: Resultsmentioning
confidence: 99%
“…The association of cancer invasion with tumor growth and metastasis was indicated by recent lysosomal proteases studies, including research on MMP-3 39 , 45 , MT1-MMP 40 , 46 , cathepsin B 47 , 48 , and cathepsin D 49 . Due to the significant effect of Arl8b on highly invasive cancer cells that survive IR, we sought to validate whether Arl8b is required for invasive tumor growth and metastasis in a mouse model.…”
Section: Resultsmentioning
confidence: 99%
“…MMPs are abundantly detected in numerous malignant neoplasms and have critical implications in almost all stages of tumour progression [2]. Recent studies have shown that aberrant MMP expression is associated with the invasion and metastasis of several malignant tumours (colorectal [3], prostate [4], liver [5], breast [6], retinoblastoma [7], and lung [8]) both in vitro and vivo. Among the MMPs, MMP7 (aka matrilysin1) is the smallest secreted proteolytic enzyme, lacking the C-terminal hemopexin domain compared with other family members, with a wide spectrum of substrate specificity against ECM components, including laminin, type IV collagen, fibronectin, and proteoglycans [9,10], as well as other molecules, such as E-cadherin, β4 integrin, tumour necrosis factor-α, and the Fas ligand [11].…”
Section: Introductionmentioning
confidence: 99%
“…In this scenario, the maturation process may orchestrate the glycosylation pathways to change glycosylation patterns according to functional needs, and may therefore also, in case of malfunctions, cause glycosylation imbalances that lead to disease, including cancer. Thus, the altered glycosylation frequently associated with cancer might both result from, and contribute to, the pathological signaling patterns typical of this disease Nguyen et al, 2017;Pinho and Reis, 2015;Stanley, 2011;Stowell et al, 2015). Our data suggest that the identification of the recycling mechanisms operating on the various enzyme modules and of the associated regulatory mechanisms will contribute significantly to our understanding of the role of Golgi dynamics in physiology and pathology.…”
Section: Discussionmentioning
confidence: 76%